2022
DOI: 10.1186/s12879-022-07112-z
|View full text |Cite
|
Sign up to set email alerts
|

Biennial surveillance of Plasmodium falciparum anti-malarial drug resistance markers in Democratic Republic of Congo, 2017 and 2019

Abstract: Background Because of the loss of chloroquine (CQ) effectiveness, the Democratic Republic of Congo (DRC)’s malaria treatment policy replaced CQ by sulfadoxine–pyrimethamine (SP) as first-line treatment of uncomplicated malaria in 2003, which in turn was replaced by artemisinin-based combination therapies (ACT) in 2005. The World Health Organization (WHO) recommends monitoring of anti-malarial drug resistance every 2 years. The study aimed to provide baseline data for biennial molecular surveill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
4
1
Order By: Relevance
“…The prevalence of pfK13 was in 7.3% this study, which was slightly higher than that reported in the previous work [20,[25][26][27][28]. Except for the A578S, which was considered as the most common pfK13 mutant alleles [29,30], we still found other 3 alleles including Q613H, C469C, and S549S. The all 3 Q613H were detected in the migrant workers from Nigeria, which was similar as reported before [31].…”
Section: Discussioncontrasting
confidence: 58%
“…The prevalence of pfK13 was in 7.3% this study, which was slightly higher than that reported in the previous work [20,[25][26][27][28]. Except for the A578S, which was considered as the most common pfK13 mutant alleles [29,30], we still found other 3 alleles including Q613H, C469C, and S549S. The all 3 Q613H were detected in the migrant workers from Nigeria, which was similar as reported before [31].…”
Section: Discussioncontrasting
confidence: 58%
“…The Pfcrt variant associated with resistance to chloroquine (CVIET) was detected in two isolates (one in Anié and one in Kouvé). This proportion is relatively low compared to other regions such as Democratic Republic of the Congo [ 63 ], Equatorial Guinea [ 64 ], and Liberia [ 54 ]. Notably, the 7G8 allele, which is predominant in South America, was detected in one isolate from Kouvé.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence refers to SNPs in Pfk13 was 7.3% in this study, which was slightly higher than that reported in the previous work [ 22 , 28 31 ]. Except for the A578S, which was considered as the most common Pfk13 mutant alleles [ 32 , 33 ], other three alleles including Q613H, C469C, and S549S were still found. The all 3 Q613H were detected in the migrant workers from Nigeria, which was similar as reported before [ 34 ].…”
Section: Discussionmentioning
confidence: 99%